Go-kart Injuries at a Fairground. Issue 5882 (29th September 1973) - Miller, Stanley S.; Proctor, David
Abstract : Twelve serious go-kart injuries were seen in three months. Almost all of these were caused by the steering wheel and all could have been prevented or their severity reduced by the use of a seat belt.